Barriers in Utilization of Maternal Health Care Services: Perceptions of Rural Women in Eastern Nepal - Lama, S; Krishna, AKI (Kathmandu University Medical Journal, 2015)
Background Nepal is promoting safe motherhood through maternity incentives schemes. Still about two-thirds of births take place at home. Inadequate access to health care and under utilization of services is the major reasons for poor health of women and children. Objectives The study aim to explore the barriers in utilization of maternal health care services in eastern Nepal specifically to explore the reasons for not availing the services and to assess the indigenous practices regarding maternal health. Methods An exploratory study design was adopted to elicit the information from the selected respondents from different villages. Focus group discussions and in-depth interviews were conducted. Data was transcribed and analyzed manually to identify themes. Results The barriers to maternal health care service utilization were identified as social factors like family pressure, superstition, shyness, misconception, negligence, illiteracy, alcoholism. Likewise, large family size, jobless, unnecessary expenditure on health services was identified as economic barrier. Some cultural practices were also found as barrier for not availing the health services. Conclusion The study explored factors that are contributing in not availing the maternal health care services. The elimination of these barriers will facilitate quality of care and health outcomes. Therefore, the interventions should be developed and implemented to improve the health status of women and children. The result of this study can be utilized to draw the attention of local government, in strategic planning related to maternal health interventions. Kathmandu University Medical Journal Vol.12(4) 2014; 253-258